PERLINDUNGAN HUKUM PENGGUNA JASA ELECTRONIC BANKING (E-BANKING) DI TINJAU DARI PERSPEKTIF HUKUM PIDANA DI INDONESIA - Aryani Witasari; Aris Setiono (Jurnal Pembaharuan Hukum, 2015)
Crime e-banking frequent one ATM card forgery. The perpetrators made a complete fake ATM cards with a magnetic stripe that already contains data records of card fraud. In addition to falsify the card, the perpetrators also know the PIN number of the card is duplicated / forged. ATM card forgery or duplication can be done because the necessary equipment to do so can be easily obtained in the market. This study uses normative legal approach by researching library materials or secondary data only, which relates to the legal protection of e-banking customers in the perspective of criminal law, using the approach of legislation, conceptual and historical. The study says that the legal protectiongiven to customers when there is a loss in e-banking transactions are bank provides its customers the facility if the losses caused by the e-banking, the bank facilitates its customers by providing legal assistance in litigation and non-litigation. 2) The legal protection of the victims of the features of e-banking in the standpoint of criminal law, is shared by the two concepts, namely the protection of the law implicitly and explicitly, of the concept of legal protection that customers have the force of law if the victim of the implications that exist within an e -banking.